Metformin dosage and galectin-3 levels: insights from PCOS patients preparing for IVF - Nikolić, Valentina N.; Stefanović, Milan; Mitić, Dejan; Sunarić, Slavica; Stojiljkovic, Vladana; Trajković, Hristina; Ignjatović, Aleksandra; Stokanović, Dragana (Frontiers in Pharmacology, 2025)
This study explores the impact of metformin dosage and hyperprolactinemia on galectin-3 levels in women with Polycystic Ovary Syndrome (PCOS), providing novel insights into their roles in the metabolic and hormonal management of the condition. A cohort of 53 women, diagnosed using the Rotterdam criteria and undergoing in vitro fertilization (IVF) preparation, was analyzed to determine how these factors influence galectin-3, a biomarker in PCOS. Using high-performance liquid chromatography to measure metformin concentrations and ELISA for galectin-3, our results revealed that both metformin dosage and hyperprolactinemia significantly statistically associated with galectin-3 levels, while body mass index (BMI) showed no significant association. These findings challenge prior assumptions and suggest that galectin-3 may be regulated via pathways independent of metformin pharmacokinetics. Notably, the correlation between galectin-3 levels and metformin concentration was either absent or weak after adjusting for the daily dose, indicating that treatment duration and dosage, rather than absolute drug levels, may more critically influence galectin-3. This study offers deeper insights into the role of personalized metformin dosing in managing PCOS, enhancing the understanding of metabolic and hormonal regulation in this condition, and laying the groundwork for future targeted therapies.